2015
DOI: 10.1063/1.4937627
|View full text |Cite
|
Sign up to set email alerts
|

The glass transition in cured epoxy thermosets: A comparative molecular dynamics study in coarse-grained and atomistic resolution

Abstract: We investigate the volumetric glass transition temperature Tg in epoxy thermosets by means of molecular dynamics simulations. The epoxy thermosets consist of the resin bisphenol A diglycidyl ether and the hardener diethylenetriamine. A structure based coarse-grained (CG) force field has been derived using iterative Boltzmann inversion in order to facilitate simulations of larger length scales. We observe that Tg increases clearly with the degree of cross-linking for all-atomistic (AA) and CG simulations. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Molecular dynamics (MD) can be used to analyze epoxies on the nanometer length‐scale to understand the influence of molecular structure on the thermo‐mechanical properties of the bulk material, as well as the interphase region arising from its usage as adhesives and composite matrices. Using MD the mechanical response of epoxies has been predicted with respect to system size, mass ratio of resin to hardener molecules, strain rate, moisture content, and temperature .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) can be used to analyze epoxies on the nanometer length‐scale to understand the influence of molecular structure on the thermo‐mechanical properties of the bulk material, as well as the interphase region arising from its usage as adhesives and composite matrices. Using MD the mechanical response of epoxies has been predicted with respect to system size, mass ratio of resin to hardener molecules, strain rate, moisture content, and temperature .…”
Section: Introductionmentioning
confidence: 99%
“…32 takes a similar stochastic reaction approach in DPD, but shows that the conversion profiles in simulations are orders of magnitude too fast with respect to experiments. Langeloth et al achieve nearly 80% cure with CG simulations accessing as much as 32 × 10 −9 s and 10 nm length-scales 33,34 . Free radical living polymerization reaction kinetic sensitivity to bonding rates are shown in systems of 24,000 DPD spheres 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, for studying cross‐linked phenolic and other thermosetting resins that hold experimental constraints for structural analysis, a theoretical approach based on molecular dynamics (MD) simulations is expected to be effective . Fueled by the evolution of computational sciences in polymer physics and the computational performance of desktop computers over the past two decades, many studies of epoxy resins using atomistic and coarse‐grained MD simulations have been reported and the modeling methodology of cross‐linked epoxy resins has been refined through these studies, revealing numerous molecular‐level findings that cannot be experimentally obtained . Progress in the computational studies of epoxy resins over the last two decades has mainly been the result of rapid industrial growth of carbon‐fiber reinforced plastics that use epoxy resins as matrix resins.…”
Section: Introductionmentioning
confidence: 99%